Simulation of the molecular dynamics of the passage of liposome with cinnarizine through the blood-brain barrier - Yulia A. Polkovnikova (Конденсированные среды и межфазные границы, 2023)
Liposomal preparations have a number of advantages: they protect the cells of the body from the toxic effects of drugs; prolong the action of the drug introduced into the body; protect medicinal substances from degradation; promote the manifestation of targeted specificity due to selective penetration from blood into tissues; change the pharmacokinetics of drugs, increasing their pharmacological effectiveness; make it possible to create a water-soluble form of a number of medicinal substances, thereby increasing their bioavailability. In this work, studies were carried out for the development of the method for determining the degree of inclusion of cinnarizine used as a corrector of cerebrovascular accidents into liposomes from soy lecithin. The aim of this study was to determine the distance between the membranes of endotheliocytes, which is critical for the passage of a liposome through the blood-brain barrier. A simulation of changes in the structure of a liposome with cinnarizine located between two cell membranes was carried out using the molecular dynamics method at various distances between the membranes. A square planar fragment of a bilayer phospholipid membrane was assembled using the Internet service Charmm-GUI->Input Generator->Martini Maker‑>BilayerBuilder (http://www.charmm-gui.org/?doc=input/mbilayer). Geometry optimization and molecular dynamics simulation were performed in Gromacs 2019 using Martini 2.2 force field. According to the results of the simulation of coarse-grained molecular dynamics, a liposome from purified soy lecithin with cinnarizine adsorbed on its inner and outer surface is able to maintain integrity, being between the membranes of endotheliocytes at a distance between membranes of more than 8 nm. When the distance between the membranes of endothelial cells is less than 8 nm, the liposome with cinnarizine located between the endotheliocytes can lose its structural integrity due to fusion with the endothelial cell membrane. As a result of the studies, the distance between the membranes of endotheliocytes was established, at which point the liposome with cinnarizine, located between endotheliocytes, can lose its structural integrity due to fusion with the endothelial cell membrane.